2015
DOI: 10.1002/pen.24251
|View full text |Cite
|
Sign up to set email alerts
|

Melt spinning of high-strength fiber from low-molecular-weight polypropylene

Abstract: Polypropylene (PP) with high melt flow index (MFI) or low molecular weight, although desired in melt spinning for enhanced productivity, is difficult to be spun into highstrength fiber using the standard process where extensive jet stretching is applied. In this work, a processing route involving minimal jet stretch has been explored. A twostage hot drawing procedure in the solid state was found to be suitable for producing high-strength fiber from lowmolecular-weight PP with an ultrahigh MFI of 115 g/10 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…71 Furthermore, Mao, Wyatt, Chien, Chen, and Yao reported that low molecular weight (high melt flow index) PP is more suitable for the melt spinning process, but the drawing/jet stretching in the melt is difficult. 72 Consequently, for low molecular weight PP, solid state drawing is a better choice. 72 In this direction, a solid state two stage hot drawing procedure was used and fibers with 600 MPa tensile strength and 1.2 GPa Young's modulus were obtained.…”
Section: Fibers Production Methodsmentioning
confidence: 99%
“…71 Furthermore, Mao, Wyatt, Chien, Chen, and Yao reported that low molecular weight (high melt flow index) PP is more suitable for the melt spinning process, but the drawing/jet stretching in the melt is difficult. 72 Consequently, for low molecular weight PP, solid state drawing is a better choice. 72 In this direction, a solid state two stage hot drawing procedure was used and fibers with 600 MPa tensile strength and 1.2 GPa Young's modulus were obtained.…”
Section: Fibers Production Methodsmentioning
confidence: 99%
“…For example, higher molecular weight polymers exhibiting higher levels of entanglement densities, have shown to display a reduction in maximum draw ratio. Conversely, processing of polymers from a disentangled state as in the case of gel-spinning of polyethylene or polypropylene has shown to lead to [40] Solid-state drawn PP 19 19.0 450 Mao [41] Solid-state drawn PP 18 11.6 580 Chatterjee [42] Gradient drawing PP 17 16.4 670 Lee [43] Drawn PP sheets 14 7.5 250 Kristiansen [44] Gel-spun PP 60 36.2 1010 Matsuo [45] Gel-spun PP -40.4 1560 Joshi [46] Solid-state drawn PP/0.5%MMT 14 15.5 730 Deng [22] Solid-state drawn PP/0.25%CNT 22 16.5 600 Bilotti [23] Solid-state drawn PP/2.5%Sep 20 16.0 550 Luijsterburg [24] Solid very high draw ratios [5]. By adding 2D nanoplatelets such as montmorillonite clays, an enormous amount of surface area is created in the nanocomposite.…”
Section: Effect Of Clay Content On Drawing Behaviour Of Oriented Tapesmentioning
confidence: 99%
“…D die and D fibers are the diameters of die and stretched fibers, respectively. Various methods are used to draw fibers like mechanical tension and air drag, 8–12 aiming at stretching the as‐spun fibers to the required fineness and orient the PP molecular or PP crystallites along the fiber direction. An improved draw ratio has a significant effect on the industrial spin line stress and induces the obvious molecular orientation and enhanced crystallization kinetics 5–7 .…”
Section: Introductionmentioning
confidence: 99%
“…At a spinning stage, a bimodal orientation was proved to exist when the take‐up speed is high, one component is parallel to fiber‐axis and another component (10%–20%) is perpendicular to fiber‐axis, 8 which leads to a lower molecular orientation and could be the reason for decreased tenacity of fibers produced at high draw‐down speed. The investigation by Mao et al 9 also reported that the DR during fiber spinning should be minimized in order to get drawn PP fibers with high tensile strength and enhanced molecular orientation in the drawing stage.…”
Section: Introductionmentioning
confidence: 99%